InterVA-4 as a public health tool for measuring HIV/AIDS mortality: a validation study from five African countries - Byass, Peter; Calvert, Clara; Nakiyingi-Miiro, Jessica; Lutalo, Tom; Michael, Denna; Crampin, Amelia; Gregson, Simon; Takaruza, Albert; Robertson, Laura; Herbst, Kobus; Todd, Jim; Zaba, Basia (Global Health Action, 2013)
Reliable population-based data on HIV infection and AIDS mortality in sub-Saharan Africa are scanty, even though that is the region where most of the world’s AIDS deaths occur. There is therefore a great need for reliable and valid public health tools for assessing AIDS mortality. Objective: The aim of this article is to validate the InterVA-4 verbal autopsy (VA) interpretative model within African populations where HIV sero-status is recorded on a prospective basis, and examine the distribution of cause-specific mortality among HIV-positive and HIV-negative people. Design: Data from six sites of the Alpha Network, including HIV sero-status and VA interviews, were pooled. VA data according to the 2012 WHO format were extracted, and processed using the InterVA-4 model into likely causes of death. The model was blinded to the sero-status data. Cases with known pre-mortem HIV infection status were used to determine the specificity with which InterVA-4 could attribute HIV/AIDS as a cause of death. Cause-specific mortality fractions by HIV infection status were calculated, and a person-time model was built to analyse adjusted cause-specific mortality rate ratios. Results: The InterVA-4 model identified HIV/AIDS-related deaths with a specificity of 90.1% (95% CI 88.7 91.4%). Overall sensitivity could not be calculated, because HIV-positive people die from a range of causes. In a person-time model including 1,739 deaths in 1,161,688 HIV-negative person-years observed and 2,890 deaths in 75,110 HIV-positive person-years observed, the mortality ratio HIV-positive:negative was 29.0 (95% CI 27.1 31.0), after adjustment for age, sex, and study site. Cause-specific HIV-positive:negative mortality ratios for acute respiratory infections, HIV/AIDS-related deaths, meningitis, tuberculosis, and malnutrition were higher than the all-cause ratio; all causes had HIV-positive:negative mortality ratios significantly higher than unity.
Keywords: HIV/AIDS; mortality; Africa; verbal autopsy; InterVA; Alpha Network